Perbedaan praktik PSN 3M Plus di kelurahan percontohan dan non percontohan program pemantauan jentik rutin kota Semarang - Dessy Nomitasari; Lintang Dian Saraswati; Praba Ginandjar (Perhimpunan Entomologi Indonesia, 2012)
In 2010 the pilot project of PJR program (routine larvae monitoring) was firstly implemented in Pedurungan village. The program was expected to increase community practice in mosquito eradication program (PSN-plus). The study was aimed to describe the difference of PSN-plus practice in pilot- and nonpilot- PJR villages. This was a comparative survey with cross sectional design. The study subject was household in pilot- and nonpilot-PJR villages which, consisted of 90 respondents each. The selection of study subject used proportional random sampling technique. To measure the of PSN-plus practice, questionnaire and observation sheet were used. Statistical analysis was performed with Chi-Square test. The result showed that PSN-plus practice in pilot village was better than nonpilot one. The statistical test proved the difference of bathtub drain (p value=0.006), closed water containers (p value=0.002), demolished used stuffs (p value=0.001), and hanging clothes habit (p value=0.0001).